PEMBERDAYAAN PEMUDA KAMPUNG KENANGA DESA GUNUNG MENYAN MELALUI INOVASI RENGGINANG MENJADI DANCANDO KENANGAN - musyaropah, wardatul; Suryani, Ermi; Amalia, Nurul; Sundari, Deva Sri (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
Village Innovation is a government program that is trying to stabilize the economy of the Indonesian people who are not doing well. People have to try harder, smarter to adapt to the economic situation. If you ignore the situation, you will crush yourself to not be able to live a normal life/needs are not met. The purpose of this community service is to reduce stunting in the Gunung Menyan Village community due to the continued rising prices and the number of people who have lost their jobs due to layoffs by several industries and companies. The Village Innovation Program in this activity brings experts in the field of entrepreneurship (collaboration of students and business lecturers). Basically, to explore the wealth of rural communities from raw materials that are less valuable into valuable products or change the wealth of consumptive communities into productive ones. The community does not have natural resources that can be empowered with less capital, but the community has the skills for entrepreneurship. In this service through the Village Innovation Program, the community is given the skills to make rangginang products with the name: Rangginang. Nutritional Carbohydrates (65%), Fat (6%) and Protein (29%). The halalness of Rangginang is guaranteed because the ingredients used are made from processed plants which are included in the positive self-declared list with the type of food made from non-risk/light risk. Halal is emphasized in the manufacturing, packaging and distribution proces